Interference of unilateral lower limb amputation on motor imagery rhythm and remodeling of sensorimotor areas - Liu, Shaowen; Fu, Wenjin; Wei, Conghui; Ma, Fengling; Cui, Nanyi; Shan, Xinying; Zhang, Yan (Frontiers in Human Neuroscience, 2022)
Purpose: The effect of sensorimotor stripping on neuroplasticity and motor imagery capacity is unknown, and the physiological mechanisms of post-amputation phantom limb pain illness remain to be investigated. Methods: In this study, an EEG-based event-related (de)synchronization (ERD/ERS) analysis was conducted using a bilateral lower limb motor imagery (MI) paradigm. The differences in the execution of motor imagery tasks between left lower limb amputations and controls were explored, and a correlation analysis was calculated between level of phantom limb pain and ERD/ERS. Results: The results of the time-frequency analysis showed that healthy controls performing the motor imagery task exhibited ERD phenomena in the mu and high beta bands, whereas amputees showed significant ERS phenomena. Phantom limb pain in amputees was significantly and negatively correlated with multiple electrode powers. Conclusion: sensorimotor abnormalities reduce neural activity in the sensorimotor cortex, while the motor imagination of the intact limb is diminished. In addition, phantom limb pain may lead to over-activation of sensorimotor areas, affecting bilateral sensorimotor area remodeling.